A tintero vuelto. - Cárdenas, María Teresa (Alfaguara, 2001)
Entrevistas con: Roberto Ampuero, Pablo Azócar, Jaime Bayly, Guillermo Blanco, Marta Blanco, Alfredo Bryce Echeñique, Carlos Cerda, Jaime Collyer, Gonzalo Contreras, Poli Délano, Ana María del Río, Marco Antonio de la Parra, Jorge Edwards, Almudena Grandes, Rafael Gumucio, Alfredo Jocelyn-Holt, Rosa Montero, Elena Poniatowska, Volodia Teitelboim, Armando Uribe y Raúl Zurita.